PENGARUH KOMITMEN AFEKTIF, NORMATIF DAN KONTINUAN TERHADAP KINERJA KARYAWAN PADA PT. SUMMIT OTO FINANCE, Tbk CAB. JAMBI - Anisah Anisah (Universitas Batanghari, 2016)
This researchaims to look at the influenceoforganizational commitment, are affective, continuance and normative commitment on employeesperformanceatPT.Summit Oto Finance,Tbk Branch Jambi. ResearchBranchuses the census method, the sample in this study is all employees. The data in this studyusing qualitative data by spreading the questionnairecoveredalternativeanswer has been provided to the respondent, and the method usingLikertSummatedRating with agivenscore.After the data iscollectedthenanalyzedto answer theproblemformulationand testhypothesesposedwith a descriptivemethodandverifikatifmethodwith multiple linearregression. The results of this researchshow thatthe affective, continuance and normative commitment quotient has significan influence to employee performance at PT. Summit Oto Finance, Tbk Branch Jambi Keywords: affective, normative and continuance commitment, performance